Modern Media in the 2024 Banda Aceh Regional Elections: Effectiveness of Use, Challenges and Impacts - Ismawan, Dana; Safrina, Safrina; Zain, Arifin (ISTIFHAM, 2024)
This study examines the use of modern media in delivering political messages during the 2024 Banda Aceh regional election, focusing on the effectiveness of social media in influencing voter behaviour. In the digital era, social media platforms such as Instagram, TikTok, and YouTube have replaced traditional methods in political campaigns. These platforms enable candidates to reach voters quickly and interactively. The research analyses how each candidate pair utilizes various modern media platforms to shape public opinion and encourage the community to vote for them in the election. Data were collected through observation, documentation, and literature review by examining and analyzing the modern media content used by each candidate pair. The findings indicate that each candidate selected platforms based on their target audience. Voter responses show that young voters are more attracted to creative content on social media such as Instagram, TikTok, Facebook, X and YouTube. In contrast, for adult voters, political messages delivered through direct and traditional campaign media, such as billboards, flyers, banners, and similar media, were more effective. However, challenges such as the spread of misinformation and the accuracy of audience targeting remain significant factors affecting campaign effectiveness. The study concludes that modern media play an essential role in supporting the delivery of political messages by each candidate pair. Nonetheless, these emerging challenges require special attention to maximize their influence on voters.